The fifth element - Willis, Bruce, 1955-; Oldman, Gary.; Holm, Ian, 1932-; Jovovich, Milla; Tucker, Chris, 1972-; Perry, Luke, 1965-; Besson, Luc.; Kamen, Robert Mark.; Ledoux, Patrice; Serra, Eric.; Columbia TriStar Home Video (Firm); Columbia Pictures; et al. (Culver City, Calif. : Columbia TriStar Home Video, 1997)
A New York City cab driver finds an alien girl who is the only one who can stop an evil force from outer space from destroying life on Earth.
Originally produced as motion picture in 1997.
Two-sided: widescreen on one side, standard on the other.
Standard format: "This film has been modified from its original version. It has been formatted to fit this screen."
Director of photography, Thierry Arbogast ; editor, Sylvia Landra ; music, Eric Serra.
Cast: Bruce Willis, Gary Oldman, Ian Holm, Milla Jovovich, Chris Tucker, Luke Perry.
MPAA rating: PG-13.
Keywords: Human-alien encounters -- Drama; Good and evil -- Drama; Life on other planets -- Drama; Taxicab drivers -- New York (State) -- New York -- Drama; New York (N.Y.) -- Drama; Video recordings for the hearing impaired